Topographies of Japanese Modernism. - Lippit, Seiji M. (Columbia University Press, 2005)
What happens when a critique of modernity -- a ""revolt against the traditions of the Western world""--Is situated within a non-European context, where the concept of the modern has been inevitably tied to the image of the West?Seiji M. Lippit o.